Immunohistochemical investigations of apoptotic and inflammatory markers in pаrodontal tissues of patients with generalized parodontitis - Samoilenko A.V.; Shpon’ka I.S.; Gorshkovа A.E.; Poslavska O.V.; Karnaukh S.O. (Морфологія, 2013)
Background. Apoptosis mechanisms should play an important role in the elimination and renewal of periodontal cells. Despite clarification of signaling cascade of apoptosis, their relationship with clinical manifestations during parodontal inflammation is almost completely unknown. Objective. To determine the immunohistochemical expression of apoptotic and inflammatory markers in marginal parodontal tissues in patients with chronic and progressive course of generalized parodontitis compared with a control group. Methods. According to clinical and morphological peculiarities of generalized parodontitis all samples were divided into 2 groups: the 1st of them included chronic course of disease, and the 2nd – progressive. Patients with intact parodontum constituted the control group. Parodontal tissues samples were studied using histological methods, cytoplasmic reaction with caspase-3 and intranuclear reaction with p21, p53, Bcl-2 and inflammatory COX-2 markers were examined. Calculations were carried out on one hundred of respective cells. These morphometric and immunohistochemical studies were subjected to statistical analysis using nonparametric indexes. Results. The course of progressive generalized periodontitis is characterized by more severe expression of inflammatory markers COX-2 and apoptotic markers caspase-3 and p21 as compared with the control group and chronic generalized periodontitis. As for antiapoptotic protein Bcl-2, a statistically significant difference was revealed only in comparison with the control group. Between two groups no significant difference was detected only in the expression levels of oncosuppressor p53 and antiapoptotic protein Bcl-2. Conclusion. Further investigations are needed to indicate the possibility to use caspase-3, p21 and COX-2 as markers of the flow activity of generalized parodontitis.